2017
DOI: 10.1073/pnas.1712418114
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational coupling in plasmonic molecules

Abstract: Plasmon hybridization theory, inspired by molecular orbital theory, has been extremely successful in describing the near-field coupling in clusters of plasmonic nanoparticles, also known as plasmonic molecules. However, the vibrational modes of plasmonic molecules have been virtually unexplored. By designing precisely configured plasmonic molecules of varying complexity and probing them at the individual plasmonic molecule level, intramolecular coupling of acoustic modes, mediated by the underlying substrate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
71
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 49 publications
2
71
0
Order By: Relevance
“…[ 7 ] A suitable nanoscale template or scaffold that is capable of holding the NPs apart at a nanoscale distance during the densification process is necessary to achieve this. [ 8,9 ] Unprecedentedly, we demonstrate a green, facile synthesis of biohybrid nanostructures using Ag/Au plasmonic NPs as sensitizers; and M13 bacteriophage as an environmental benign virus template. Genetically engineered M13 bacteriophage, with a length of ≈880 nm and diameter of 6.6 nm, could function as a biological scaffold for the controlled assembly of NPs because of its filamentous geometry, [ 10–12 ] high aspect ratio, and outstanding chemical properties.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 7 ] A suitable nanoscale template or scaffold that is capable of holding the NPs apart at a nanoscale distance during the densification process is necessary to achieve this. [ 8,9 ] Unprecedentedly, we demonstrate a green, facile synthesis of biohybrid nanostructures using Ag/Au plasmonic NPs as sensitizers; and M13 bacteriophage as an environmental benign virus template. Genetically engineered M13 bacteriophage, with a length of ≈880 nm and diameter of 6.6 nm, could function as a biological scaffold for the controlled assembly of NPs because of its filamentous geometry, [ 10–12 ] high aspect ratio, and outstanding chemical properties.…”
Section: Figurementioning
confidence: 99%
“…The LSPR enhancement arising from the controlled densification of metallic NPs (as in the case of NP‐M13 assemblies) has also been observed in other plasmonic molecules assemblies. [ 8,9 ] The instability of biomolecules (virus/DNA) derived metamaterials has often been a major concern especially for application in organic optoelectronic devices because of the tendency of biomolecules to disintegrate under intense light irradiation. [ 23–25 ] To investigate the illumination effect on the optical properties of the NP‐M13 nanogap assemblies, a simple light stability test was conducted.…”
Section: Figurementioning
confidence: 99%
“…When assembled closely, these individual plasmon modes of nanoparticles strongly interact with each other to form new collective modes, resembling the atomic orbitals hybridization in molecules [6]. Therefore, assembled metallic nanoparticles are also referred to as plasmonic molecules [7,8]. Recently, many concepts in chemistry have been readily applied to plasmonic molecules such as stereoisomers [9], vibrational coupling [8] and group theory [10], providing new insights into light-surface plasmon interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, assembled metallic nanoparticles are also referred to as plasmonic molecules [7,8]. Recently, many concepts in chemistry have been readily applied to plasmonic molecules such as stereoisomers [9], vibrational coupling [8] and group theory [10], providing new insights into light-surface plasmon interactions. More interestingly, very much analogous to phenomena in molecular systems including electromagnetically induced transparency [11,12] and Fano resonance [13][14][15] have been observed in plasmonic molecules, rendering many promising applications in slow lights [11], chemical/bio-sensing [16,17], and nanolasers [18].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, microRNAs (miRNAs) have been reported to be implicated in the morphogenesis and homoeostasis of skin and its appendages (5,6). Yi et al (7) demonstrated that miRNAs play an important role in mammalian skin development, as evidenced by findings showing that the epithelium-specific depletion of miRNA biogenesis by the genetic disruption of the dicer or dgcr8 genes leads to barrier defects, abnormal hair follicle development and hyperproliferation of basal interfollicular keratinocytes.…”
Section: Introductionmentioning
confidence: 99%